1966
DOI: 10.1083/jcb.31.3.429
|View full text |Cite
|
Sign up to set email alerts
|

ULTRASTRUCTURAL FEATURES OF BETA LEAVES INFECTED WITH BEET YELLOWS VIRUS

Abstract: A cytochemical and electron microscope study has been made of leaves of sugar beet infected with beet yellows virus. Inclusions of particles, which agree in size with beet yellows virus particles isolated by other investigators, have been localized in the ground cytoplasm, in the chloroplasts, and in the nuclei. These particles are circa 100 A in diameter and have an electron-transparent core of 30 to 40 A. Use of acridine orange, azure B, and pyronine Y has revealed that the cytoplasmic inclusion bodies, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The Type C pattern appeared similar to that of phytoferritin as described by Hyde et al (1963), by Cronshaw et al (1966), and by Robards and Humpherson {i()(i'j). The last-named indicated that phytoferritin is normally present only in cells at an early stage of differentiation or in plastids incapable of full photosynthetic activity.…”
Section: Resultssupporting
confidence: 61%
“…The Type C pattern appeared similar to that of phytoferritin as described by Hyde et al (1963), by Cronshaw et al (1966), and by Robards and Humpherson {i()(i'j). The last-named indicated that phytoferritin is normally present only in cells at an early stage of differentiation or in plastids incapable of full photosynthetic activity.…”
Section: Resultssupporting
confidence: 61%
“…At periods of 5,6,8,9,11,12,13, and 15 days after inoculation, the diseased tissue was dissected into 1-rnm squares and placed in 3% glutaraldehyde in 0.05 M potassium phosphate buffer at pH 6.8 for 19 h. Dissection of tissue was carried out 2 h after the start of each daily light period. After fixation, the tissue was rinsed in several changes of the buffer for 1 h and postfixed in 2% Os04 in 0.05 M phosphate buffer at pH 6.8 for 2 h. After dehydration in an acetone series and propylene oxide, the material was embedded in a plastic mixture consisting of Epon, Araldite, and dodecenyl succinic anhydride in the ratio 3:3:8 by volume, using dimethyl phthalate 30 as an accelerator.…”
Section: Methodsmentioning
confidence: 99%
“…1961;Rossner, 1960;Schnepf, 1961), viral inclusions (Cronshaw et al, 1966) or just electron dense inclusions (Sprey et al, 1976)?…”
Section: Where When and Why Plant Ferritin?mentioning
confidence: 97%
“…Such patterns, lamellae-disks alternating within the plastidal inclusion organized in F-4 array have been observed by several investigators. Cronshaw et al (1966) and Kim and Fulton (1969) have alternatively interpreted such crystalline pattern as viral rod particles or filaments, respectively. Scattered particles (S) and square (SQ) arrays are also visible in this micrograph.…”
Section: Plant Ferritin Aggregate Arrangement and Distributional Pattmentioning
confidence: 98%
See 1 more Smart Citation